Structural property, surface area and electrical conductivity activated carbon from biomass materials and various manufacturer in Malaysia - R., Mohamad Yunus; N., Hashim; M., Deraman; A., Mohd. Ramli (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.